Inverse modelling of the reversely magnetized, shallow plumbing system hosting oil reservoirs of the Auca Mahuida volcano (Payeina retroarc, Neuquén Basin, Argentina). Issue 2 (11th December 2015) - Paine, John; De Ritis, Riccardo; Ventura, Guido; Longo, Mariana; Ravat, Dhananjay; Speranza, Fabio; Chiappini, Massimo
Abstract: The Auca Mahuida volcano (2.03–0.88 Ma) located east of the Andean thrust front in the Neuquén basin (Argentina) hosts an oil system of thermogenic origin and is affected by the NW–SE striking-faults. Intrusive bodies and the underlying Jurassic sediments constitute the reservoir rocks. Aeromagnetic data collected in the Auca Mahuida area detected multiple dipolar magnetic anomalies, many of which have reverse polarity. Palaeomagnetic measurements on rock samples collected in the field together with available age determinations indicate that the reversely magnetized sources were mainly emplaced during the Matuyama reverse polarity chron while the normal polarity sources were emplaced during the Olduvai and/or Jaramillo subchrons. The location and geometry of the intrusive bodies is poorly known and the customary magnetic inversion is rendered difficult because of multiple natural remanent magnetization directions. To address these difficulties, a voxel inversion was applied to model the vector residual magnetic intensity (VRMI) transformation of the observed total magnetic intensity data. The modelling showed a 1.5 km deep, subcircular ring-shaped intrusion below the summit of the volcano and a series of NW–SE elongated, fault-controlled intrusive bodies to depths up to 3–4 km. Our results show that magnetic data and VRMI modelling help resolve the geometry of the shallow plumbing system of volcanoes with remanently magnetized sources, and estimate the depth and geometry of potential oil reservoirs in volcanic areas.